2021
DOI: 10.26434/chemrxiv.14362238
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Low-Valent Tungsten Redox Catalysis Enables Controlled Isomerization and Carbonylative Functionalization of Alkenes

Abstract: Tungsten catalysis has played an instrumental role in the history of organometallic chemistry, with electrophilic, fully oxidized W(VI) catalysts featuring prominently in olefin polymerization and metathesis reactions. Here, we report that the simple W(0) precatalyst, W(CO)<sub>6</sub>, catalyzes the isomerization and hydrocarbonylation of alkenes via a W(0)/W(II) redox couple. The 6- to 7-coordinate geometry changes associated with this redox process are key in allowing isomerization to take place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 29 publications
0
3
1
Order By: Relevance
“…These results support the notion that alkene isomerization proceeds via a 1,3-hydride shift. This is in contrast with our previous method, which gave terminal D-incorporation consistent with a 1,2-hydride shift pathway. Conducting the reaction without HBpin corroborated previous studies that showed the ability of W(0) to promote isomerization via 1,3-H shift without external hydride sources. , In addition, the lack of deuterium incorporation at the β-C­(sp 3 ) site argues against a 1,1-hydroboration of a Fischer-type W-carbene.…”
contrasting
confidence: 99%
See 3 more Smart Citations
“…These results support the notion that alkene isomerization proceeds via a 1,3-hydride shift. This is in contrast with our previous method, which gave terminal D-incorporation consistent with a 1,2-hydride shift pathway. Conducting the reaction without HBpin corroborated previous studies that showed the ability of W(0) to promote isomerization via 1,3-H shift without external hydride sources. , In addition, the lack of deuterium incorporation at the β-C­(sp 3 ) site argues against a 1,1-hydroboration of a Fischer-type W-carbene.…”
contrasting
confidence: 99%
“…Although Koh recently leveraged the stabilizing features of π-benzyl intermediates to promote a homobenzylic borylation, the means to enable C–B bond formation through alkylmetal stabilization at less-activated sp 3 sites via chain-walking still remain elusive. On the basis of recent findings by our group, where a W-catalyst and bidentate directing group were used to control an isomerization–hydrocarbonylation reaction, we wondered whether we could expand this strategy to enable a W-catalyzed C­(sp 3 )-borylation controlled by native directing groups at C­(sp 3 )–H sites that are beyond reach in conventional chain-walking events (Scheme b) . Such a method would complement existing approaches toward β-boryl carbonyl compounds in terms of scope and chemoselectivity .…”
mentioning
confidence: 99%
See 2 more Smart Citations